Holder De Polder Festival. (Assenede, : Gemeentebestuur, 1987)
Audenaert, Peter ; Braeckman, Dirk ; Brandts, Erik ; Borsten, Henric ; Callens, Mario ; Cardon, Marcel ; Cauwelier, Willy ; Clarysse, Véronique ; Coucke, Remi ; Coucke, René ; De Blok, Luc ; De Coster, Jean ; De Greve, Maria ; De Houck, Willy ; De Leener, Hugo ; De Rudder, Nora ; De Smet, Eric ; De Vierman, Freddy ; Dey, Han ; Gees, Paul ; Gobyn, Luc ; Hioco, Marc ; Leyman, Marc ; Martel, Alain ; Merckaert, Patrick ; Mertens, Pierre ; etc.
Catalogus + programmaboekje
Holder De Polder Festival, Assenede, 22 t/m 30 augustus 1987
boek